Clinical presentation with consequences and laboratory diagnosis of multi and extensive drug resistance in typhoid cases - Mehmood, Mehwish sajjad; Fatima, Ambreen; Ahmed, Iftekhar; Khan, Fouzia Zeeshan; Gohar, Hareem; Salman, Salma (International Journal of Pathology, 2024)
Background: Enteric fever is among the major problem in the health care settings of developing countries like Pakistan. Unjudicial use and over the counter availability of antibiotics lead to the emergence of multi drug resistant and extensive drug-resistant strains of salmonella outbreak which demonstrate severity of disease of the disease. Our objective is to determine the clinical presentation, consequences and antibiotic susceptibility patterns of Multi Drug Resistant (MDR) typhoid and Extensive drug resistance (XDR) typhoid cases.Methods: The study was conducted in the department of Microbiology, Dow Diagnostic Reference and Research Laboratory, Dow University of Health Sciences. All laboratory proven Salmonella positive cultures samples were selected from laboratory that were either fully or partially treated, or were taking anti-Salmonella. Clinical trends along with clinical outcomes were assessed from clinical presentation. Furthermore, Demographic details were noted. Detailed history about the presenting illness with examination findings and medications were recorded.Results: A total of 333 patients had positive blood culture for enteric fever, in which maximum number of XDR cases 84% (n=281) were observed in blood cultures followed by MDR salmonella in 16 % (n=52). Meropenem and azithromycin didn’t show any resistance in our study.Conclusion: Our study has demonstrated that pediatric population is more vulnerable for developing salmonella infection. Carbapenems and azithromycin are among the last choices for the treatment of XDR cases. Analysis of our results imply stress on the implementation of preventive measures for spread of enteric fever including proper diagnosis, vaccination and good sanitation system